Pengaruh Literasi Keuangan, Pendapatan Serta Locus Of Control, Terhadap Keputusan Investasi Pada Karyawan PT. PLN (Persero) Up3 Bali Utara Singaraja - Riska Diah Megayanti; Made Pradana Adiputra (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2021)
This study aims to determine the effect of financial literacy, income, and locus of control on the investment decisions of employees of PT. PLN UP3 North Bali Singaraja. This research is a type of quantitative research with a total of 110 respondents. Data obtained by distributing questionnaires using google form media. The sample was selected using criteria with purposive sampling technique. The data used are primary data in the form of respondents' answers and processed using SPSS version 20. The results of this study indicate that financial literacy has a positive and significant effect on investment decisions of employees of PT PLN UP3 Bali Utara Singaraja, income has a positive and significant effect on investment decisions of employees of PT. PLN UP3 Bali Utara Singaraja, and locus of control have a positive and significant effect on employee investment decisions at PT PLN UP3 Bali Utara Singaraja.